2017
DOI: 10.3390/rs9030234
|View full text |Cite
|
Sign up to set email alerts
|

Bohai Sea Ice Parameter Estimation Based on Thermodynamic Ice Model and Earth Observation Data

Abstract: Abstract:We estimate two essential sea ice parameters-namely, sea ice concentration (SIC) and sea ice thickness (SIT)-for the Bohai Sea using a combination of a thermodynamic sea ice model and Earth observation (EO) data from synthetic aperture radar (SAR) and microwave radiometer. We compare the SIC and SIT estimation results with in-situ measurements conducted in the study area and estimates based on independent EO data from near-infrared/optical instruments. These comparisons suggest that the SAR-based disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 71 publications
0
23
0
Order By: Relevance
“…We also tested the usefulness of some textural features. In our earlier studies, we observed that spatial autocorrelation ( [32,33]) and entropy ( [8,34,35]) are effective in SAR classification. Here, we computed them in a window size at a scale of 5.5 km in both polarizations.…”
Section: Featuresmentioning
confidence: 96%
“…We also tested the usefulness of some textural features. In our earlier studies, we observed that spatial autocorrelation ( [32,33]) and entropy ( [8,34,35]) are effective in SAR classification. Here, we computed them in a window size at a scale of 5.5 km in both polarizations.…”
Section: Featuresmentioning
confidence: 96%
“…Although these satellite data cover the study area with a fairly high spatial resolution (~1 km), they are typically limited in temporal resolution and provide only one image covering the study area per day, which are constrained by the proportion of cloud-free images of the MODIS and the AVHRR data being mostly less than 20% [5,15]. Synthetic aperture radar (SAR) data is also commonly used to monitor sea ice, which has also been applied to detecting ice types and thickness in the Bohai Sea due to their fine spatial resolution and insensitivity to cloud interference [17][18][19]. However, the SAR data are limited by a long repeat cycle (6-44 days) [20].…”
Section: Bandmentioning
confidence: 99%
“…In the training, MODIS R 1 data set the OW and SI miss-classification percentages were below 0.5%. The R 1 imagery has the best possible MODIS resolution of 250 m. Previously also, another simple algorithm, the reflectance ratio (R r ) between bands 1 and 2 has been used for the OWSI classification [69,70]. We found that this ratio is sometimes contaminated by a detector striping artefact (see [71]) in the R 2 image which leads to false SI detection.…”
Section: Discussionmentioning
confidence: 95%
“…We have previously conducted OWSI classification in the Bohai Sea using the reflectance ratio ( ) between bands 1 and 2 [69]. SI was detected with < 1.8.…”
Section: Open Water-sea Ice Classificationmentioning
confidence: 99%